Epigenetic effects of natural polyphenols: A focus on SIRT1‐mediated mechanisms. Issue 1 (23rd July 2013) - Ayissi, Vincent B. Owona; Ebrahimi, Azadeh; Schluesenner, Hermann
<x xml:space="preserve">Abstract</x> Polyphenols are a class of natural compounds widely distributed in fruits, vegetables, and plants. They have been reported to possess a wide range of activities in prevention and alleviation of various diseases like cancer, neuroinflammation, diabetes, and aging. Polyphenols are effective against chronic diseases and recent reports indicated strong epigenetic effects of polyphenols. Most of the studies investigating epigenetic effects of natural polyphenols have focused on their beneficial effects in cancer treatment. However, epigenetic defects have been demonstrated in many other diseases as well, and application of polyphenols to modulate the epigenome is becoming an interesting field of research. This review summarizes the effects of natural polyphenols in modulating epigenetic‐related enzymes as well as their effect in prevention and treatment of chronic diseases with a focus on SIRT1 modulation. We have also discussed the relation between the structure and function of epigenetic‐modifying polyphenols.